ANTECEDENT VARIABLE KUALITAS LAPORAN KEUANGAN YANG DIMEDIASI KOMPLEKSITAS BANK - Nanang Agus Suyono (Politeknik Sawunggalih Aji, 2019)
This study aims to analyze the effect of tenure, the size of the public accounting firm and the auditor's specializationon the quality of financial statements with the complexity of the bank as a moderating variable. The population in this study is the annual financial statements of the banking industry that are listed on theIndonesia Stock Exchange in the period of 2014 to 2016. The sampling technique in this study was carried out bypurposive sampling method, to obtain 21 banks as research samples. The analytical method used in this study is logisticregression and multiple regression analysis with the help of SPSS Statistics v.22 software. The results of this study indicate that auditor specialization has a positive effect on the quality of financialstatements. The size of a public accounting firm has a negative effect on the quality of financial statements. Tenure of apublic accounting firm does not affect the quality of financial statements. The complexity of banks moderates therelationship of tenure of public accounting firms to the quality of financial statements. The complexity of banks does notmoderate the relationship between the size of the public accounting firm and the auditor's specialization of the qualityof financial statements.